Penerapan Teknologi Untuk Digitalisasi Administrasi dan Keuangan Desa Harjasari Berbasis Web - Ni Wayan Parwati Septiani; Lukman Lukman; Alusyanti Primawati (LPPM Universitas Bina Sarana Informatika, 2026)
Praktik pengelolaan administrasi dan keuangan di lingkungan Rukun Tetangga (RT) pada umumnya masih mengandalkan pencatatan manual, yang berisiko menimbulkan ketidaktepatan data, keterlambatan pelaporan, serta rendahnya transparansi. Permasalahan tersebut juga dialami oleh RT 01 RW 11 Desa Harjasari dalam mengelola data kependudukan dan kas warga. Melalui kegiatan pengabdian kepada masyarakat ini, tim pelaksana menerapkan teknologi tepat guna berupa sistem aplikasi berbasis web untuk mendukung proses digitalisasi administrasi dan keuangan RT. Metode pelaksanaan meliputi observasi kebutuhan mitra, perancangan dan pengembangan sistem, pelatihan penggunaan aplikasi, serta pendampingan implementasi di lapangan. Sistem yang dikembangkan mampu mengelola data warga, pencatatan iuran, transaksi kas masuk dan keluar, serta menghasilkan laporan keuangan secara otomatis. Hasil kegiatan menunjukkan adanya peningkatan efisiensi kerja pengurus RT, ketertiban administrasi, dan kemudahan dalam pemantauan kondisi keuangan. Selain itu, literasi digital pengurus dan warga juga mengalami peningkatan seiring penggunaan sistem secara langsung. Implementasi teknologi ini berkontribusi dalam mewujudkan tata kelola RT yang lebih transparan, akuntabel, dan adaptif terhadap perkembangan teknologi di era digital dan industri 4.0. Administrative and financial management practices in neighborhood associations (Rukun Tetangga/RT) are generally still conducted using manual record-keeping methods, which may lead to data inaccuracies, delays in reporting, and low transparency. This problem is also experienced by RT 01 RW 11 in Harjasari Village in managing population data and residents’ financial contributions. Through this community service activity, the implementation team introduced an appropriate technology solution in the form of a web-based application system to support the digitalization of RT administrative and financial management. The implementation method included needs observation with community partners, system design and development, training on application usage, and field implementation assistance. To measure the effectiveness of the program, an evaluation was conducted using pre-test and post-test assessments for RT administrators regarding their understanding of digital system usage, which showed an increase in the average score from 55% in the pre-test to 88% in the post-test. In addition, a system trial was conducted during the implementation phase to manage resident data and record financial transactions. The trial results indicated that the system was able to accelerate administrative recording processes by approximately 70% compared to manual methods. User acceptance was also evaluated through a user satisfaction survey, showing that 90% of respondents stated that the system was easy to use, 87% felt that the system helped administrative tasks, and 85% believed that financial reports became more transparent and easier to monitor. Overall, the implementation of this system improved the efficiency of RT administrators’ work, enhanced administrative order, and supported more transparent, accountable, and technology-adaptive governance in the neighborhood environment in the era of digital transformation and Industry 4.0.